Proton Transport in Hierarchical-Structured Nafion Membranes: A NMR Study - Yang, H.; Zhang, Jin; Li, J.; Jiang, San Ping; Forsyth, M.; Zhu, H. (American Chemical Society, 2017)
© 2017 American Chemical Society. It is known that hierarchical structure plays a key role in many unique material properties such as self-cleaning effect of lotus leaves and the antifogging property of the compound eyes of mosquitoes. This study reports a series of highly ordered mesoporous Nafion membranes with unique hierarchical structural features at the nanometer scale. Using NMR, we show for the first time that, at low RH conditions, the proton in the ionic domains migrates via a surface diffusion mechanism and exhibits approximately 2 orders of magnitude faster transport than that in the nanopores, whereas the nanopores play a role of reservoir and maintain water and thereby conductivity at higher temperature and lower humidities. Thereby creating hierarchical nanoscale structures is a feasible and promising strategy to develop PEMs that would enable efficient electrochemical performance in devices such as fuel cells, even in the absence of high humidity and at elevated temperatures.